Біоплато для очищення водних об'єктів від важких металів - Лапань, О.В.; Міхєєв, О.М. (Доповіді НАН України, 2019)
Розроблено мобільну конструкцію біоплато для очищення водних об'єктів від важких металів, де як біотичний компонент використовуються вищі наземні рослини. Показано ефективність запропонованої гідрофітної споруди з рослинами тимофіївки лучної щодо хрому(VI), іонів кадмію(II) і цинку(II). Досліджено
вплив хрому(VI) на ростові параметри рослин тимофіївки лучної. A mobile bioplateau design for the purification of water bodies from heavy metals has been developed, where
higher land plants are used as the biotic component. To construct a bio plateau, chemically inert floating materials
are used as the substrate granular foam, on whose top the seeds of higher terrestrial plants are placed.
The constructed bioplateaux on the 9th day of incubation were placed into tanks with a solution of heavy
metals to study the cleaning efficiency of timothy in the aquatic environment. For the study of the influence of
chro mium (VI) on growth parameters of timothy, the bioplateaux were placed in desiccators with tap water,
which additionally introduced potassium bichromate. The measurements of the length of the stems and roots
were carried out at the 8th and 13th days of incubation of the bioplateau in the solution. The efficiency of
the proposed hydrophytic structure with timothy plants meadow with respect to chromium (VI), cadmium
ions (II) and zinc (II) is shown. A study of the effect of chromium (VI) on the growth parameters of timothy
grass plants is conducted. Разработана мобильная конструкция биоплато для очистки водных объектов от тяжелых металлов, где в
качестве биотического компонента используются высшие наземные растения. Показана эффективность
предложенного гидрофитного сооружения с растениями тимофеевки луговой по отношению к хрому(VI),
ионам кадмия(II) и цинка(II). Проведено исследование влияния хрома(VI) на ростовые параметры растений тимофеевки луговой.